The Impact of Lung Ventilation on Some Cytokines after Coronary Artery Bypass Grafting. (March 2017) - Toikkanen, V.; Rinne, T.; Nieminen, R.; Moilanen, E.; Laurikka, J.; Porkkala, H.; Tarkka, M.; Mennander, A.
Background and Aims: Cardiopulmonary bypass induces a systematic inflammatory response, which is partly understood by investigation of peripheral blood cytokine levels alone; the lungs may interfere with the net cytokine concentration. We investigated whether lung ventilation influences lung passage of some cytokines after coronary artery bypass grafting. Material and Methods: In total, 47 patients undergoing coronary artery bypass grafting were enrolled, and 37 were randomized according to the ventilation technique: (1) No-ventilation group, with intubation tube detached from the ventilator; (2) low tidal volume group, with continuous low tidal volume ventilation; and (3) continuous 10 cm H2 O positive airway pressure. Ten selected patients undergoing surgery without cardiopulmonary bypass served as a referral group. Representative pulmonary and radial artery blood samples were collected for the evaluation of calculated lung passage (pulmonary/radial artery) of the pro-inflammatory cytokines (interleukin 6 and interleukin 8) and the anti-inflammatory interleukin 10 immediately after induction of anesthesia (T1), 1 h after restoring ventilation/return of flow in all grafts (T2), and 20 h after restoring ventilation/return of flow in all grafts (T3). Results: Pulmonary/radial artery interleukin 6 and pulmonary/radial artery interleukin 8 ratios ( p = 0.001 and p = 0.05, respectively) decreased, while pulmonary/radial artery interleukin 10 ratio ( p = 0.001) increased in patients without cardiopulmonary bypass as compared with patients with cardiopulmonary bypass. Conclusions: The pulmonary/radial artery equation is an innovative means for the evaluation of cytokine lung passage after coronary artery bypass grafting. The mode of lung ventilation has no impact on some cytokines after coronary artery bypass grafting in patients treated with cardiopulmonary bypass.